Spatial dimension of public administration - Ocampo, Romeo B. (2004)
The Spatial Dimension of Public Administration (SDPA) has been given renewed importance in recent times. This is widely reinforced by the incorporation of Information Communications Technology (ICT) in governance, which transformed geographical patterns from a boundary and time based to time-space compressed administration. This has several implications: 1) globalization made bordersporous; 2) nations-states shared sovereignty with international organizations and superpower countries and; 3) information, people, money and technology could travel a much faster pace. On the other hand, definite influences in Public Administration (PA) result in "horizontalization" and "deterritorialization." Of similar impact is the use of geographic information system (GIS) which provides empirical accuracy in PA practice and in policy research. Despite the said developments, information divide is still a big factor to consider in the utilization of SDPA. This article traces the development of SDPA in the history of PA theories and its implications in the major trends of globalization.
Keywords: Geographic information sytems; Information and communication technologies; Public administration; Spatial Information Management; Spatial systems; Transportation; National College of Public Administration and Governance